Clinical Features and Potential Mechanisms Relating Neuropathological Biomarkers and Blood-Brain Barrier in Patients With Alzheimer’s Disease and Hearing Loss - Zhang, Wei-jiao; Li, Dan-ning; Lian, Teng-hong; Guo, Peng; Zhang, Ya-nan; Li, Jing-hui; Guan, Hui-ying; He, Ming-yue; Zhang, Wen-jing; Zhang, Wei-jia; Luo, Dong-mei; Wang, Xiao-min; et al. (Frontiers in Aging Neuroscience, 2022)
Background The aim of this study was to explore clinical features and potential mechanisms relating neuropathological biomarkers and blood-brain barrier (BBB) in Alzheimer’s disease (AD) and hearing loss (HL). Materials and Methods A total of 65 patients with AD were recruited and auditory function was assessed by threshold of pure tone audiometry (PTA). Patients were divided into AD with HL (AD-HL) and AD with no HL (AD-nHL) groups based on the standard of World Health Organization. Clinical symptoms were assessed by multiple rating scales. The levels of neuropathological biomarkers of β amyloid1-42 (Aβ1–42) and multiple phosphorylated tau (P-tau), and BBB factors of matrix metalloproteinases (MMPs), receptor of advanced glycation end products, glial fibrillary acidic protein, and low-density lipoprotein receptor related protein 1 were measured. Results (1) Compared with AD-nHL group, AD-HL group had significantly impaired overall cognitive function and cognitive domains of memory, language, attention, execution, and activities of daily living (ADL) reflected by the scores of rating scales (P < 0.05). PTA threshold was significantly correlated with the impairments of overall cognitive function and cognitive domains of memory and language, and ADL in patients with AD (P < 0.05). (2) P-tau (S199) level was significantly increased in CSF from AD-HL group (P < 0.05), and was significantly and positively correlated with PTA threshold in patients with AD. (3) MMP-3 level was significantly elevated in CSF from AD-HL group (P < 0.05), and was significantly and positively correlated with PTA threshold in patients with AD (P < 0.05). (4) In AD-HL group, P-tau (S199) level was significantly and positively correlated with the levels of MMP-2 and MMP-3 in CSF (P < 0.05). Conclusion AD-HL patients have severely compromised overall cognitive function, multiple cognitive domains, and ADL. The potential mechanisms of AD-HL involve elevations of AD neuropathological biomarker of P-tau (S199) and BBB factor of MMP-3, and close correlations between P-tau (S199) and MMP-2/MMP-3 in CSF. Findings from this investigation highly suggest significance of early evaluation of HL for delaying AD progression, and indicate new directions of drug development by inhibiting neuropathological biomarkers of AD and protecting BBB.